REPRESENTASI PEREMPUAN DALAM MEDIA SOSIAL: ANALISIS KONSTRUKSI GENDER PADA AKUN TIKTOK @FEMINIYOU - Rarame, Agnes Octavia; Riswandi (Prodi Ilmu Komunikasi Universitas Putera Batam, 2025)
This research examines the representation of feminine energy on the TikTok account @feminiyou and its perception among Generation Z women. Employing a qualitative phenomenological approach, the study explores the subjective interpretations of informants regarding feminine energy content on social media. The results reveal that @feminiyou’s content serves beyond mere entertainment or information, acting as a platform for emotional, spiritual, and social reflection for young women. Through themes of self-love, healing, and empowerment of feminine identity, informants integrate these values into their personal lives. The portrayal by @feminiyou reflects a dynamic gender construction, redefining femininity as an authentic and empowering inner strength, unbound by conventional stereotypes. These findings underscore the role of social media as a digital safe space for fostering female empowerment in the modern era.